Exploring critical success factors of competence-based synergy in strategic alliances: The Renault-Nissan-Mitsubishi strategic alliance - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2021)
This paper aims to unbundle the antecedents of competence-based synergy in the strategic alliance formation process by employing the ARCTIC framework. The current research provides a new empirical application of the ARCTIC framework to reveal the success factors of reciprocal synergies of the Renault-Nissan-Mitsubishi strategic alliance in the automotive industry. By taking a resource-based view on the sources of competitive advantage, the current paper contributes to theoretical and practical issues of global strategic alliances as part of the existing literature on strategic management, international business, and corporate finance. By bridging qualitative and quantitative research methods, the paper provides validity to the ARCTIC framework with an application of the real option valuation. A conceptual model of research helps practitioners and scholars to explore critical success factors of alliance formation and to predict a competence-based synergy of strategic alliances. Future research may explore the institutional context of strategic alliances, specifically, exploring the impact of the French and Japanese governments on the Renault-Nissan-Mitsubishi alliance's synergies.
Keywords: 330; core competence; real options; strategic alliance; synergy; the ARCTIC framework